2019
DOI: 10.4081/oncol.2019.403
|View full text |Cite
|
Sign up to set email alerts
|

MCT4 has a potential to be used as a prognostic biomarker - a systematic review and meta-analysis

Abstract: The role of several metabolic changes, such as hypoxia and acidosis, in the tumour environment has caught the attention of researchers in cancer progression and invasion. Lactate transport is one of the acidosis-enhancing processes that are mediated via monocarboxylate transporters (MCTs). We conducted a systematic review and meta-analysis to investigate the expression of two cancer-relevant MCTs (MCT1 and MCT4) and their potential prognostic significance in patients with metastasis of different types of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 78 publications
3
18
0
1
Order By: Relevance
“…Indeed, we observed that the expression of MCT4 was the highest among the four lactate transporters (Supplementary Fig. S1 ) and high expression of MCT4 was associated with poor prognosis in BLCA (HR 1.43, p = 0.02), CESC (HR 2.0, p = 0.01), LIHC (HR 1.9, p = 6e−4) and LUAD (HR 1.83, p = 8e−5), corroborating previous data 24 ⁠. MCT-4 is also the transporhat was identified to regulate glycolytic flux 15 ⁠.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, we observed that the expression of MCT4 was the highest among the four lactate transporters (Supplementary Fig. S1 ) and high expression of MCT4 was associated with poor prognosis in BLCA (HR 1.43, p = 0.02), CESC (HR 2.0, p = 0.01), LIHC (HR 1.9, p = 6e−4) and LUAD (HR 1.83, p = 8e−5), corroborating previous data 24 ⁠. MCT-4 is also the transporhat was identified to regulate glycolytic flux 15 ⁠.…”
Section: Resultssupporting
confidence: 90%
“…MCT-4 is considered to be particularly suited for the export of lactate from highly glycolytic cells; additionally, MCT-4 has low a nity for pyruvate, suggesting this transporter to be particularly suited for cancer cells that are known to exhibit high NAD+/NADH ratio 23 . Indeed, we observed that the expression of MCT4 was the highest among the four lactate transporters (Supplementary Figure 1) and high expression of MCT4 was associated with poor prognosis in BLCA (HR 1.43, p=0.02), CESC (HR 2.0, p = 0.01), LIHC (HR 1.9, p=6e-4) and LUAD (HR 1.83, p=8e-5), corroborating previous data 24 . MCT-4 was also the transporter that was identi ed to regulate glycolytic ux 15 .…”
Section: Deregulation Of Transporterssupporting
confidence: 90%
“…Unexpectedly, our results demonstrated that CUP patients with positive GLUT1 and CAIX expression presented significantly higher overall survival, and the same was observed for the co-expression of these proteins with MCT4 and MCT1/CD147 co-expression. Currently, most studies in the literature have shown that hyperglycolytic tumors present a poorer prognosis and decreased survival rates ( 38 , 39 , 45 , 46 ). Conversely, our results indicate a different behavior of this metabolic phenotype in CUP.…”
Section: Discussionmentioning
confidence: 99%